2018
DOI: 10.1002/adsc.201800607
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Mediated Photoredox‐Catalyzed N‐Arylation of NH‐Sulfoximines with Electron‐Rich Arenes

Abstract: The direct C−H/N−H dehydrogenative cross‐coupling of NH‐sulfoximines with electron‐rich arenes was realized by oxidative visible‐light photoredox catalysis, applying 9‐mesityl‐10‐methylacridinium perchlorate as an organic photocatalyst. Sulfoximines display diverse desirable properties for medicinal chemistry and the pharmaceutical industry. However, their preparation is still challenging. Our reaction proceeds without sacrificial oxidant, at room temperature and is highly selective for the C−N bond forming re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 82 publications
(22 reference statements)
0
34
0
Order By: Relevance
“…Some of us have been for a long time involved in the development of transformations related to those derivatives with a focus on S ‐perfluoroalkyl sulfoximine compounds and their N ‐functionalization . Recently, N ‐halo sulfoximines have demonstrated their abilities to trigger upon light irradiation the generation of nitrogen‐centered sulfoximidoyl radicals ,. The first report pointing out this reactivity was described by Oae and co‐workers .…”
Section: Methodsmentioning
confidence: 99%
“…Some of us have been for a long time involved in the development of transformations related to those derivatives with a focus on S ‐perfluoroalkyl sulfoximine compounds and their N ‐functionalization . Recently, N ‐halo sulfoximines have demonstrated their abilities to trigger upon light irradiation the generation of nitrogen‐centered sulfoximidoyl radicals ,. The first report pointing out this reactivity was described by Oae and co‐workers .…”
Section: Methodsmentioning
confidence: 99%
“… 311 Wimmer and König in 2018 reported the photocatalytic dehydrogenative N -arylation of NH -sulfoximines with electron-rich arenes ( Scheme 98 ). 312 Optimized reaction conditions showed that the joint action of N -Me Mes-Acr + ClO 4 – photocatalyst ([ Acr-1 ]ClO 4 ) and the Co(III) proton-reduction catalyst [Co(dmgH) 2 PyCl] in MeCN under a nitrogen atmosphere best catalyzed this transformation. Oxygen or other chemical oxidants instead of the Co co-catalyst gave significantly reduced product yields.…”
Section: N -Centered Radical Generation From N–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
“…This Acr photocatalyst has a sufficiently oxidizing photoexcited state ( E 1/2 *PC + /PC • = +1.88 V vs SCE in PhCN) 74 to allow for thermodynamically favorable ET with both reaction components (e.g., for diphenyl N H-sulfoximine, E p/2 ox = +2.00 V vs SCE in MeCN; for p -xylene, E p/2 ox = +2.01 V vs SCE in MeCN). 312 Based on these observations and literature precedent for the operation of joint photoredox/cobaloxime hydrogen-evolution catalysis, the following mechanistic model was proposed involving two separate turns of a photoredox catalytic cycle and a two-photon requirement. Upon photoexcitation of the Acr photocatalyst, the resulting photoexcited state undergoes ET with either the sulfoximine or arene substrate to yield the respective radical cation intermediate.…”
Section: N -Centered Radical Generation From N–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
“…One of the first pioneering work of photoredox catalyzed direct N ‐arylation of sulfoximines with electron rich arenes has been successfully demonstrated by König and co‐workers (Scheme 12). [26] Optimization conditions revealed that 20 mol % of 9‐mesityl‐10‐methylacridinium perchlorate as photocatalyst, 10 mol% of Co(dmgH) 2 PyCl as proton reducing catalyst in degassed acetonitrile (0.1 M) under nitrogen atmosphere in presence of 455 nm blue light irradiation for 20 hours, leading to dispense the arylated sulfoximines in decent yields. Both, steric factor and electronic effect of the substituents on arene coupling partner had pivotal role for controlling the regioselectivity such as 4‐ tert butyl toluene furnished only one regio‐isomer in excellent yield due to the stabilization of radical‐cation intermediate.…”
Section: N−h Functionalizationsmentioning
confidence: 99%